Variations in Sources, Composition, and Exposure Risks of PM2.5 in both Pre-Heating and Heating Seasons - Dingyuan Yang; Zhiyong Li; Ziyuan Yue; Jixiang Liu; Zhen Zhai; Zelin Li; Minglei Gao; Ailian Hu; Wenjia Zhu; Ning Ding; Zhenxin Li; Songtao Guo; et al. (Aerosol and Air Quality Research)
Abstract “Clean Heating” (CH) was promoted in 2017 in north China. Nevertheless, CH impacts on PM2.5 chemical components, sources, and health risks in small cities remain unclear. A field measurement was taken at an urban site within the central Beijing-Tianjin-Hebei (BTH) region covering the pre-heating season (PHS) and heating season (HS) in the winter of 2019. PM2.5 concentrations (in µg m−3) increased from 69.1 in the PHS to 129 in the HS, reflecting the impacts of heating activities. Water-soluble ions dominated in terms of PM2.5, accounting for 32.0% in the PHS and 42.3% in the HS, respectively. On average, SO42− and NO3− (in µg m−3) were found to be markedly enhanced from 3.54 and 11.1 in the PHS to 13.1 and 23.2 in the HS, especially in the case of SO42−, reflecting the increased usage of coal/natural gas. Meanwhile, the ratios of NO3−/SO42− dropped from 2.75 in the PHS to 2.08 in the HS, implying drastic SO42− emissions from coal combustion used for heating. This may have been associated with the re-burning of coal for heating despite the “coal banning” law. Total carcinogenic risks (CRs) posed by inhalation of heavy metals increased from 6.61 × 10−6 in children and 2.64 × 10−5 in adults in the PHS to 8.23 × 10−6 and 3.29 × 10−5 in the HS. In contrast, the non-CRs for children and adults decreased in the HS due to a reduction in Ba of 85.5% in the HS. A total of seven sources, including fugitive dust (FD), vehicle exhaust (VE), coal combustion (CC), secondary inorganic aerosol (SIA), industrial emissions (IE), glass production (GP), and biomass burning (BB), were identified using a PMF model. The GP fraction decreased from 29.6% in the PHS to 2.59% in the HS due to strict emission control, which concurred with the decrease in Ba. The CC contribution increased significantly from 2.42% to 16.9%, indicating the CC was still serious in HS. Furthermore, the elevated BB share in the HS suggested that biomass was still being used as heating fuel.